Function of Centriolar Satellites and Regulation by Post-Translational Modifications - Renaud, Clotilde C. N.; Bidère, Nicolas (Frontiers in Cell and Developmental Biology, 2021)
Centriolar satellites are small membrane-less granules that gravitate around the centrosome. Recent advances in defining the satellite proteome and interactome have unveiled hundreds of new satellite components thus illustrating the complex nature of these particles. Although initially linked to the homeostasis of centrosome and the formation of primary cilia, these composite and highly dynamic structures appear to participate in additional cellular processes, such as proteostasis, autophagy, and cellular stress. In this review, we first outline the main features and many roles of centriolar satellites. We then discuss how post-translational modifications, such as phosphorylation and ubiquitination, shape their composition and functions. This is of particular interest as interfering with these processes may provide ways to manipulate these structures.